Peran Guru dalam Membentuk Karakter Religius Siswa - Rahmah Rahmah (Journal on Education, 2023)
Teachers have an important role in education, especially in cultivating the religious character of students. This is because teachers often deal directly with students in the learning process. In addition, teachers can also encourage children to discover, explore and reconstruct their knowledge as much as possible so that later in society they can live independently and be able to work. Religious character is a person's character, character, morals, or attitude and behavior which is formed from the internalization of various policies based on religious teachings. This study aims to describe the teacher's role in shaping the religious character of students. This research was conducted using a qualitative descriptive method, using written data obtained from searching documents, journals and books. From the results of the study it was found that the teacher has an important role in shaping the religious character of students. The teacher's role is to educate, teach, guide, direct, train, assess and evaluate students. In forming the religious character of students, teachers need to create habits through special activities that are mandatory for students to participate in, including (1) requiring students to pray before starting and ending learning. (2) Schedule various extracurricular special religious activities.